PENGALAMAN LESBIAN DALAM RUANG-RUANG KOMUNIKASI - Rustinawati, Yuli (Jurnal Pekommas, 2022)
Communication spaces function to recognize themselves, to know each other, to share stories, and to meet partner are very limited for lesbians. Spaces are silenced. There had been efforts to open those spaces by the lesbian community and organizations since the 1990s. However, they also struggled to exist as they come and go, lesbian then joined gay communities that were already present and growing. Assuming it gave them more space and opportunities to grow. However, those spaces were not home for lesbians. Following the 1998's reformation, information became more open and accessible. The internet became a tool for lesbians to create safe online spaces. They started organizing face-to-face meetings and ended their silence. The purpose of this study is to get an overview of the spaces created by lesbian groups to get to know each other and learn from one another. This study uses a qualitative method, internet searching is the method used in collecting research data. The results of this study identified that the existing communication spaces are able to provide the information needed by lesbians and break the silence, but these spaces were not sustainable.  Therefore, there is a great need for safe and sustainable spaces for lesbians to continue to express and share themselves and to be heard.